2010
DOI: 10.1021/jp102194u
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Dispersed Kinetics of Dichlorofluorescein in Potassium Hydrogen Phthalate Crystals

Abstract: The connection between photoluminescence (PL) intermittency and excited-state kinetics is explored for 2',7'-dichlorofluorescein (DCF) isolated in crystals of potassium acid phthalate (KAP) using time-tagged, time-resolved, time-correlated single-photon counting (T3R-TCSPC). In this technique, PL intermittency or "blinking" is measured in conjunction with the time of photon arrival relative to photoexcitation, allowing for the correlation of emissive intensities and excited-state decay kinetics of single molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…It should be noted that using time-tagged, time-correlated single photon counting we have established that the variation in on-state intensities is due to both discrete changes in the non-radiative decay rate and changes in the absorption cross-section due to spectral diffusion. 50 Applying this definition to the data presented in Fig. 1, the molecule undergoes 16 switches, and resides in five different intensity states within the first 50 s of this trace.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that using time-tagged, time-correlated single photon counting we have established that the variation in on-state intensities is due to both discrete changes in the non-radiative decay rate and changes in the absorption cross-section due to spectral diffusion. 50 Applying this definition to the data presented in Fig. 1, the molecule undergoes 16 switches, and resides in five different intensity states within the first 50 s of this trace.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has been investigating the role of proton transfer in the PI exhibited by rhodamine-type chromophores isolated in single crystals of potassium acid phthalate (KAP) [102,109113]. Comparative studies of violamine R (VR) emission in PVOH and KAP found that the temperature dependence of VR PI was markedly different in these two environments.…”
Section: Photoluminescence Intermittency In Organic Luminophoresmentioning
confidence: 99%
“…A second (and less appreciated) aspect of SM emission is the presence of emissive states of variable intensity. Fluctuations in emissive intensity have been found to coincide with changes in the excited-state lifetime, [36][37][38] and spectral jumps. 39 Discrete emissive states were first statistically identified by Watkins and Yang, and quantified by the change point detection (CPD) algorithm.…”
Section: Resultsmentioning
confidence: 88%
“…Early PL intermittency studies were limited to systems that demonstrated a single emissive state. Recently, more complex distributions of on-state intensities have been observed 38,40,43,44 that frequently follow power-law distributed emissive and non-emissive state durations. The observation of a power-law is consistent with dispersed kinetics for dark-state production and decay.…”
Section: Discussionmentioning
confidence: 99%